ANALISIS KONTRIBUSI FINANCIAL TECHNOLOGY UNTUK MENINGKATKAN TINGKAT LITERASI KEUANGAN (STUDI KASUS PEDAGANG PASAR AUR KOTA BUKITTINGGI) - Sherly Oktaviani; Sandra Dewi (CV. Adiba Aisha Amira, 2024)
The background of this research is to look at the contribution of fintech to increasing the level of financial literacy among Aur Market traders in Bukittinggi City. This fintech will have an impact on a business, both positive and negative impacts. Apart from that, fintech also plays a role in reducing the financial solution. The aim of the research is to determine and analyze the contribution of fintech to increasing the level of financial literasi in Aur Market Bukittinggi City. The research method used by the author here is qualitative, research with the key informants for this research being the Aur Market traders in Bukittinggi City, totaling 8 informants. In collecting data, research used observation, interrvews and documentation methods. The research result obtained from the analysis of the contribution of fintech in increasing the level of financial literacy in Aur Market Bukittinggi City are that the contribution of fintech is quite good and running well. Where Aur Market Bukittinggi City are already using fintech as a transaction tool with cotumers. Using fintech will make transaction more pratical, faster and easer, and fintech provide features to track user expenses, income and assets. So this can make users see their financial situation more clearly, beside that our financial security will be well maintained so there is no need to wotrry